2005
DOI: 10.1002/ejoc.200500101
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of Difluoromethyl Alcohols from Both Enolizable and Non‐Enolizable Carbonyl Compounds with Difluoromethyl Phenyl Sulfone

Abstract: A general and efficient nucleophilic difluoromethylation of carbonyl compounds (both enolizable and non-enolizable aldehydes and ketones) has been achieved by using a nucleophilic (phenylsulfonyl)difluoromethylation-reductive desul-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Therefore, we embarked on a systematic study on the potential of using reagent 1 as a nucleophilic difluoromethylation (CF 2 H-transferring) reagent for aldehydes and ketones through a (phenylsulfonyl)difluoromethylation-reductive desulfonylation protocol (Scheme 6, Eq. (14)) [32]. This two-step difluoromethylation method was found to be amenable to a variety of structurally diverse aldehydes and ketones.…”
Section: Using Phso 2 Cf 2 H Reagent (1)mentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, we embarked on a systematic study on the potential of using reagent 1 as a nucleophilic difluoromethylation (CF 2 H-transferring) reagent for aldehydes and ketones through a (phenylsulfonyl)difluoromethylation-reductive desulfonylation protocol (Scheme 6, Eq. (14)) [32]. This two-step difluoromethylation method was found to be amenable to a variety of structurally diverse aldehydes and ketones.…”
Section: Using Phso 2 Cf 2 H Reagent (1)mentioning
confidence: 97%
“…Inspired by Dolbier's work on nucleophilic trifluoromethylation of 1,2-cyclic sulfates [38], we have successfully carried out an efficient nucleophilic fluoroalkylation of cyclic sulfates 36 and sulfamidates 37 with PhSO 2 CF 2 H (1)/LiHMDS/ HMPA system (Scheme 10) [39]. These regioselective reactions Since (phenylsulfonyl)difluoromethyl carbanion (PhSO 2 CF 2 À ) belongs to hard nucleophiles, its reaction with a,b-unsaturated ketones (a,b-enones) generally proceeds in a 1,2-addition mode [32,40]. However, recently we found that both solvent and the structure of a,b-enones (44) can influence the 1,2-/1,4-addition ratio (Table 1) [40].…”
Section: Using Phso 2 Cf 2 H Reagent (1)mentioning
confidence: 98%
See 1 more Smart Citation
“…The difluoromethyl moiety has been widely used to modify physical, chemical and biological properties of organic molecules. Although, several methods for the synthesis of difluorometylated derivatives are available [7][8][9][10][11][12][13], only few protocols of FMST synthesis on a large scale have been reported to date [14][15][16]. According to the literature synthetic strategies the difluoromethyl α-substituted styrene was prepared by two-step procedure, where a key step involved a nucleophilic addition of Page 6 of 17 A c c e p t e d M a n u s c r i p t either Gringard's reagent (phenylmagnesium bromide [14]) or organolithium (methyllithium [15]) to corresponding gem-difluorinated ketones.…”
Section: *Manuscriptmentioning
confidence: 99%
“…Meanwhile, difluoromethylation with difluoromethyl phenyl sulfone (PhSO 2 CHF 2 ) [18] is less effective for enolizable aldehydes and ketones. On the basis of these drawbacks, difluoro(trimethylsilyl)methyl phenyl sulfone 24 has been developed for the more effective difluoromethylation of carbonyl compounds.…”
Section: Difluoro(trimethylsilyl)methyl Phenyl Sulfonementioning
confidence: 99%